2008
DOI: 10.1177/0363546508324177
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Iatrogenic Injury to the Peroneal Nerve during Posterolateral Femoral Tunnel Placement in Double-Bundle Anterior Cruciate Ligament Reconstruction

Abstract: During posterolateral femoral tunnel placement, the risk of injury to the common peroneal nerve is minimal but is increased as the knee is placed in less flexion. Guide pin placement at knee flexion of 120 degrees is recommended to ensure safety of the peroneal nerve and the biceps tendon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…During this travelling fellowship, the majority of the femoral tunnels were drilled independently from the anteromedial portal (Figure 2). The key concerns with anteromedial portal drilling are: short femoral tunnel length, injury to the cartilage, injury to posterolateral knee structures and posterior wall blow-out [70-72]. …”
Section: Discussionmentioning
confidence: 99%
“…During this travelling fellowship, the majority of the femoral tunnels were drilled independently from the anteromedial portal (Figure 2). The key concerns with anteromedial portal drilling are: short femoral tunnel length, injury to the cartilage, injury to posterolateral knee structures and posterior wall blow-out [70-72]. …”
Section: Discussionmentioning
confidence: 99%
“…Cadaveric studies have shown that the risk of common peroneal nerve injury significantly increases when creating femoral tunnels through the low-accessory anteromedial portal at a low angle such as 70°of knee flexion. For that reason, a higher angle of more than 110°of knee flexion is recommended to avoid peroneal nerve injury when creating a femoral tunnel through the low medial accessory portal [65,66]. Surgeons should consider those risks during drilling.…”
Section: Drilling Tunnelsmentioning
confidence: 99%
“…In a laboratory setting, flexion of the knee to a minimum of 110 degrees and preferably over 120 degrees was necessary to obviate this possibility. 10,11 Clinically, there is slight variability in knee anatomy and in anteromedial portal placement that can impact these measurements. It is preferable to place the anteromedial portal just superior to the tibial plateau and just lateral to the medial condyle.…”
Section: Central Anatomic Single-bundle Surgical Techniquementioning
confidence: 99%